The Effect of Service Quality, Price, and Facilities on Consumer Satisfaction of Excellent Group Lamongan Tourism Bus - Ali Makhmud; Mohammad Yaskun; Evi Fitrotun (Jurnal Price : Ekonomi dan Akuntasi, 2024)
This study aims to analyze the effect of service quality, price, and facilities on consumer satisfaction with Excellent Group Lamongan tourism buses. This research applied a quantitative approach. The population consisted of 10,800 consumers of Excellent Group Lamongan tourism buses during November 2023 to April 2024. The sample included 100 respondents determined using the Slovin formula and simple random sampling. Primary data were collected through a Likert-scale questionnaire, supported by secondary data from the management of PT. Excellent Empat Saudara Group. The data were analyzed using IBM SPSS version 24 through validity testing, reliability testing, classical assumption testing, multiple linear regression, coefficient of determination, t-test, and F-test. The results indicate that service quality has a positive and significant effect on consumer satisfaction (t = 3.920; sig. = 0.000), price has a positive and significant effect (t = 3.128; sig. = 0.002), and facilities have a positive and significant effect (t = 3.309; sig. = 0.001). Simultaneously, the three variables significantly affect consumer satisfaction (F = 13.777; sig. = 0.000). The R Square value of 0.301 indicates that 30.1% of the variation in consumer satisfaction can be explained by service quality, price, and facilities. Service quality is the most dominant factor based on the highest standardized beta value.